Learning from the voices and life trajectories of our most able students: A listening guide analysis. (January 2020) - Killas, Harry; Lo, C Owen; Porath, Marion; Tan, Yuen Sze Michelle; Hsieh, Chia-Yen; Ralph, Rachel
The "Superkids, " a group of highly gifted students, were first portrayed in a 2004 documentary. In response to the question of what happened to these students after the original film, a second documentary has been produced. The sequel focused on these individual's lives, their retrospective insights about gifted education, their educational and career choices, and their reflections on their early adulthood. Transcripts of filmed interviews were analyzed using The Listening Guide, a qualitative method for understanding and interpreting voices. The researchers further highlighted first-person voices that may not have been apparent in interviews. This information was used to identify contrapuntal voices among the participants that reflected their views on the meaning of giftedness and their experience of studying in full-time congregated gifted programs. These voices provided a foundation for understanding the variety of pathways to accomplishment, the meaning of the gifted label, and the purpose of education at large.